THEORETICAL BASIS OF PROBLEM OF SHAPING CREATIVE COMPETENCE IN FUTURE SOCIAL WORKERS FOR WORK WITH GIFTED CHILDREN - Halyna Mykhailyshyn; Oksana Protas ("Scientific Information Agency "Science-technologies-information" LLC, 2019)
For effective forming of creative competence in future social work experts, we suggested using the creative approach to organization of educational process in a higher educational establishment, using the potential of different disciplines in the process of professional training. We clarified the main aspects of shaping of creative competence in future social workers in classroom and outside classroom, as well as main forms of the methodology of such training. The use of the mentioned approaches will give an opportunity to shape creative competence in future social workers for work with gifted children.